An investigation into the effects of winning the Malcolm Baldrige National Quality Award on the performance of hospitals/healthcare systems - Unger, Kevin L., author; Cobb, Brian, advisor; Chermack, Thomas, committee member; Hartley, Nancy, committee member; Hudnut, Paul, committee member (Colorado State University. Libraries, 2013)
The efficiency and efficacy of the U.S. healthcare system has been in question for decades. We spend more per capita than any other industrialized nation while consistently realizing inferior health outcomes for our population as a whole when compared with many industrialized nations. In 1965, the proportion of U.S. gross domestic product (GDP) attributed to healthcare was approximately 6%. Today, the share of GDP spent on healthcare by the United States is almost 18%. This number is 5% higher than the next two countries, the Netherlands and France (spending 12.0% and 11.8% of their GDP on healthcare respectively) according to the Organization for Economic Co-operation and Development (OECD). The proportion of GDP spent on healthcare in 2020 is estimated to reach 20%, with the nation's increasing healthcare expeditors reducing resources available for other worthy government programs, eroding wages, and undermining the competitiveness of U.S. industry. This dissertation explores longitudinal outcome data for Malcolm Baldrige National Quality Award recipients in healthcare in the dimensions of patient outcomes (mortality, complications and patient safety), as well as hospital financial and efficiency measures (average length of stay, expense per discharge and profitability). Source data from Truven Health Analytics (formerly Thomson Reuters) are used to evaluate changes in level, immediacy/latency and trend in the years prior to versus the years after becoming a Malcolm Baldrige National Quality Award recipient. In support of the hypothesis, being a recipient of the Malcolm Baldrige National Quality Award in healthcare explains slight enhancements in clinical outcomes, while hospital financial and efficiency measures all showed overwhelmingly positive operating results.
Keywords: Baldrige; healthcare; management; process improvement; quality; total quality management